Regulatory T cells confer a circadian signature on inflammatory arthritis - L. E. Hand (Nature Portfolio, 2020)
Circadian rhythms can alter inflammatory state and activity of inflammatory diseases such as rheumatoid arthritis. Here the authors show that extrinsic signals confer a circadian rhythm to regulatory T cell activity, which in turn drives rhythmic inflammation in collagen-induced arthritis.